SYSTEMATIC LITERATURE REVIEW: CITY BRANDING AND CITY IMAGE IN SUPPORT OF THE DEVELOPMENT OF THE IMAGE OF THE AGRO-TOURISM AREA AND BUNG KARNO MEMORABILIA IN BLITAR CITY, INDONESIA - Poerwati, Titik; Gai, Ardiyanto Maksimilianus; Witjaksono, Agung; Sasongko, Ibnu; Hamka, Hamka; Mulyadi, Lalu; Firtanto, Natan Waskito; Desderius, Kevie (Journal of Architecture, Planning and Construction Management, 2025)
This study aims to conduct a systematic literature review on the concepts of city branding, city image, and city identity, and how these three elements can support the development of the image of agro-tourism areas in Blitar City. With the increasing interest in agro-based tourism, it is essential to understand how effective branding can enhance the attractiveness and identity of the region. The methodology employed in this research involves a comprehensive literature analysis, gathering and evaluating various relevant studies. This review encompasses multiple aspects, including successful branding strategies, public perceptions of city image, and the factors that shape city identity. The findings indicate that the integration of city branding and the development of agro-tourism image can create positive synergies, enhance tourist appeal, and strengthen local identity. The results of this study are expected to provide recommendations for stakeholders in Blitar City in designing more effective branding strategies and developing policies that support the growth of the agro-tourism sector. Thus, this research not only contributes to academic literature but also offers practical guidance for sustainable tourism development in the region.